Comparative analysis of 1-D river flow models applied in a quasi 2-D approach for floodplain inundation prediction - Villazón, Mauricio; Timbe, Luis; Willems, Patrick (Maskana, 2013)
A comparative analysis was performed of three 1-D river hydrodynamic models (Mike 11, InfoWorks-RS and HEC-RAS) in a quasi 2-D setting. The study area was schematized either as a network of fictitious river branches or as storage areas. The models were run on a reduced area of the Dender River basin in Belgium, respectively for three historical flood events and eight synthetic events with a return period between 1 and 1000 years. The performance of the models were tested comparing simulated discharge, water level, inundation volume and inundated area. Results show that the three models and the two approaches used for the presentation of the floodplain lead to very similar results with a root mean square error of around 6 cm for the peak river levels and 2% for the river discharges. Despite the high accuracy of the water levels in the main river, inundation levels inside the floodplains have root mean square errors of around 25 cm during flood conditions.